Nucleotide Evolution, Domestication Selection, and Genetic Relationships of Chloroplast Genomes in the Economically Important Crop Genus Gossypium - Zhou, Tong; Wang, Ning; Wang, Yuan; Zhang, Xian-Liang; Li, Bao-Guo; Li, Wei; Su, Jun-Ji; Wang, Cai-Xiang; Zhang, Ai; Ma, Xiong-Feng; Li, Zhong-Hu (Frontiers in Plant Science, 2022)
Gossypium hirsutum (upland cotton) is one of the most economically important crops worldwide, which has experienced the long terms of evolution and domestication process from wild species to cultivated accessions. However, nucleotide evolution, domestication selection and genetic relationship of cotton species remain largely to be studied. In this study, we used chloroplast genome sequences to determine the evolutionary rate, domestication selection, and genetic relationships of 72 cotton genotypes (36 cultivated cotton accessions, seven semi-wild races of G. hirsutum, and 29 wild species). Evolutionary analysis showed that the cultivated tetraploid cotton genotypes clustered into a single clade, which also formed a larger lineage with the semi-wild races. Substitution rate analysis demonstrated that the rates of nucleotide substitution and indel variation were higher for the wild species than the semi-wild and cultivated tetraploid lineages. Selection pressure analysis showed that the wild species might have experienced greater selection pressure, whereas the cultivated cotton genotypes underwent artificial and domestication selection. Population clustering analysis indicated that the cultivated cotton accessions and semi-wild races have existed the obviously genetic differentiation. The nucleotide diversity was higher in the semi-wild races compared with the cultivated genotypes. In addition, genetic introgression and gene flow occurred between the cultivated tetraploid cotton and semi-wild genotypes, but mainly via historical rather than contemporary gene flow. These results provide novel molecular mechanisms insights into the evolution and domestication of economically important crop cotton species.